Research Trends in Developing Communicative Arabic Teaching Materials through QR Code Integration and Monopoly-Based Gamification: A Systematic Literature Review - Nab'han Hadyan Adnan; Yusuf Hanafi; Imam Asrori; Abdul Basid; Abang Hadzmin Abang Taha (Universitas Ahmad Dahlan, 2026)
This study aims to analyze research trends in the development of communicative Arabic teaching materials integrated with digital technology. The review also examines how QR Code technology and gamification have been incorporated within this broader development trend. The method used is Systematic Literature Review with reference to the PRISMA procedure which includes the identification, selection, eligibility, and inclusion stages. The data source was obtained through national and international scientific articles published in the 2022–2026 range and according to the topics of communicative teaching materials, digital technology-based learning, and gamification of Arabic language learning. The results of the study have shown the development of Arabic teaching materials still tends to lead to the integration of digital technology to increase interactivity and student involvement. In addition, a communicative approach has proven to be an important foundation in supporting the mastery of Arabic language skills in a contextual manner. Furthermore, the application of gamification, especially through educational games such as monopoly, shows significant potential in increasing learning motivation and active participation of students. However, there are still research gaps related to the simultaneous integration of communicative teaching materials, QR Code technology, and monopoly games in one complete learning design. Therefore, this research provides important implications as a conceptual basis in the development of innovative Arabic teaching materials that are able to integrate communicative approaches, digital technology, and gamification to improve the quality of Arabic language learning.